A Step Subsequent to Preinitiation Complex Assembly at the Ribosomal RNA Gene Promoter Is Rate Limiting for Human RNA Polymerase I-Dependent Transcription - Panov, Kostya I. (American Society for Microbiology, 2001)
The assembly, disassembly, and functional properties of transcription preinitiation complexes (PICs) of human RNA polymerase I (Pol I) play a crucial role in the regulation of rRNA gene expression. To study the factors and processes involved, an immobilized-promoter template assay has been developed that allows the isolation from nuclear extracts of functional PICs, which support accurate initiation of transcription. Immunoblotting of template-bound factors showed that these complexes contained the factors required to support initiation of transcription, SL1, upstream binding factor (UBF), and Pol I. We have demonstrated that, throughout a single round of transcription, SL1 and UBF remain promoter bound. Moreover, the promoter-bound SL1 and UBF retain the ability to function in transcription initiation. SL1 has a central role in the stable association of the PIC with the promoter DNA. The polymerase component of the PIC is released from the promoter during transcription yet is efficiently recycled and able to reinitiate from “poised” promoters carrying SL1 and UBF, since the PICs captured on the immobilized templates sustained multiple rounds of transcription. Kinetic analyses of initiation of transcription by Pol I revealed that Pol I-dependent transcription is rate limited in a step subsequent to recruitment and assembly of Pol I PICs. The rate of RNA synthesis is primarily determined by the rates at which the polymerase initiates transcription and escapes the promoter, referred to as promoter clearance. This rate-limiting step in Pol I transcription is likely to be a major target in the regulation of rRNA gene expression.